Integrating cultural lean practices with innovations to advance quick changeover for enhanced productivity in compressor manufacturing in Thailand - Sirikasemsuk, Kittiwat; Kiatcharoenpol, Tossapol; Luanwiset, Darin; Rattanapuchong, Pradthana; Leerojanaprapa, Kanogkan (International Journal of Innovative Research and Scientific Studies, 2025)
This study integrated cultural lean practices with innovations to enhance efficiency and streamline quick changeovers in a compressor manufacturing organization. Monthly production of compressor housing components consistently fell short of targets due to excessive changeover times, which averaged 4,733 seconds (approximately 1.31 hours) per model, impacting overall production efficiency. To address this issue, the study combined traditional lean and Single-Minute Exchange of Die (SMED) techniques, such as shifting tasks from internal to external processes, a well-known method for reducing changeover time. In addition, new innovations were introduced, including the development of an M24 T-slot bolt clamp to expedite the setup process and the design of die stoppers to enable rapid and precise die placement. A steel forklift wheel stop was also installed to aid in the proper alignment and positioning of equipment. These improvements resulted in a 61.86% reduction in changeover time, lowering the average time to 1,805 seconds (0.514 hours) per model. The findings emphasized that innovation-driven lean practices not only simplified tasks for workers but also supported their engagement and productivity, contributing to long-term organizational success.